2018
DOI: 10.3126/jnhrc.v16i3.21425
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Experience and Coping Strategies among Cancer Patients Receiving Chemotherapy

Abstract: Background:  Cancer is considered one of the foremost common causes of death. Fatigue is among the distressing symptoms for cancer patients receiving chemotherapy. Adequate coping is essential for individual to deal with the effects of cancer related treatment. The objective of the study was to find out the fatigue experience and coping strategies among cancer patients receiving chemotherapy.Methods: A descriptive, cross-sectional research design was used for the study. The samples was taken from day care and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Our finding that patients in both the Very High morning and evening fatigue classes used self-distraction to cope with fatigue is not unexpected. Self-distraction was identified as an effective coping strategy for fatigue in oncology patients during CTX [20], in patients with ESKD [44], and in healthy working adults [50]. Self-distraction may be used to shift the focus from fatigue without eliminating or treating the symptom [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that patients in both the Very High morning and evening fatigue classes used self-distraction to cope with fatigue is not unexpected. Self-distraction was identified as an effective coping strategy for fatigue in oncology patients during CTX [20], in patients with ESKD [44], and in healthy working adults [50]. Self-distraction may be used to shift the focus from fatigue without eliminating or treating the symptom [50].…”
Section: Discussionmentioning
confidence: 99%
“…Coping is often described in terms of the use of engagement (e.g., actively doing something to alter the stressor) or disengagement (e.g., avoidance) strategies [16][17][18]. In the four studies that examined the association between coping and fatigue during CTX, greater fatigue severity was associated with disengagement coping [19,20], while lower fatigue severity was associated with engagement coping [21,22], However, these studies did not examine the impact of cumulative exposure to SLEs on coping and fatigue. One study found that increased exposure to SLEs was associated with greater fatigue severity in women with breast cancer; however, the effects of coping were not evaluated [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown significant fatigue and coping issues with patients with cancer in Nepal who are receiving chemotherapy. 27 Addressing the quality of life of these patients should be another important policy agenda for Nepal.…”
Section: Cancer In Nepalmentioning
confidence: 99%
“…The FSI has been used previously in a study on kidney failure population 45. This instrument was translated into the Nepali language, and has a Cronbach’s alpha of 0.79 46…”
Section: Discussionmentioning
confidence: 99%
“…45 This instrument was translated into the Nepali language, and has a Cronbach's alpha of 0.79. 46 Secondary outcomes Secondary outcomes are other CKD symptoms, occupational performance and HRQoL, which will be measured at Time 0 (Baseline) and Time 3 (Week 12).…”
Section: Primary Outcome Fatiguementioning
confidence: 99%